COMPARISON OF MORPHOLOGICAL AND REPRODUCTIVE PROPERTIES OF LIPPIZANER MARES IN STUD FARM RAISING AND ON FAMILY FARMS - Tomo Rastija (Poljoprivreda, 2000)
This paper aimed at determination of defferences in morphological and reproductive properties of Lippizaner breed blood mares raised in stud farm Đakovo and on family farms. Results of morphological properties investigation indicate better development of investigated body measures of a stud farm mares, except chest width that was more pronounced in family farm mares. Significant differences were determined with withers height (cattle tape), back height and cannon bone circumference whereas differences of withers height (stick), small of the back height, chest depth and chest width were highly significant. As for reproductive properties stud farm raising mares were older at first fertilization and first foaling compared to the family farm mares. Statistically very significant differences in pregnancy duration were determined only at 5-12 pregnancy of stud farm raising mares. First, second, fourth and 5-12 service period lasted longer in stud farm raising mares whereas longer duration of the second and third service period was determined with family farm mares.